To solve this system of equations, we can use the method of substitution or elimination.
I will use the substitution method here:
From the second equation, we can express y in terms of x:
y = 32 + 6x
Now, we can substitute this expression for y in the first equation:
4x - 8(32 + 6x) = -36
4x - 256 - 48x = -36
-44x - 256 = -36
-44x = 220
x = -5
Now that we have found the value of x, we can substitute it back into one of the original equations to find the value of y:
-6(-5) + y = 32
30 + y = 32
y = 32 - 30
y = 2
Therefore, the solution to the system of equations is x = -5 and y = 2.
Solve the system of equations 4X minus 8Y equals -36 negative 6X plus Y equals 32
1 answer